Residual symptoms and lower lung function in patients recovering from SARS-CoV-2 infection - Trinkmann, Frederik; Müller, Michael; Reif, Alexandra; Kahn, Nicolas; Kreuter, Michael; Trudzinski, Franziska; Eichinger, Monika; Heußel, Claus Peter; Herth, Felix (The European respiratory journal, 2021)
Tweetable abstract ERSpublications - click to tweetAbout half of the patients recovering from SARS-CoV-2 have persistent symptoms and lower lung function as long as 2 months after infection. This is common even in younger SARS-CoV-2 convalescents with few comorbidities. https://bit.ly/38dyCYB